2017
DOI: 10.7454/epidkes.v1i2.1805
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Obesitas dengan Kejadian Hipertensi Derajat 1 di Pos Pembinaan Terpadu Penyakit Tidak Menular (Posbindu PTM) Kantor Kesehatan Pelabuhan Bandung Tahun 2016

Abstract: Hipertensi sampai saat ini masih menjadi masalah kesehatan di dunia termasuk Indonesia. Prevalensi hipertensi di Indonesia, cukup tinggi yaitu sebesar 25,8% (Riskesdas, 2013). Sebagian besar penderita hipertensi termasuk dalam kelompok hipertensi derajat 1 dan separuhnya tidak menyadari sebagai penderita. Hipertensi bukan penyakit kausal tunggal, ada berbagai faktor yang berkontribusi terhadap munculnya hipertensi, salah satunya yang sering ditemukan adalah obesitas. Penelitian ini bertujuan untuk mengetahui b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 3 publications
2
7
0
6
Order By: Relevance
“…Thus, it can be said that the probability of occurrence of hypertension in adults aged 26-45 years in Medan which obesity, is four times greater than those who are not obese. This is in line with the study of Rohkuswara (2016) in the city of Bandung with AOR = 1.681 and P-value = 0.031 [18]. Obesity has become an epidemic today.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it can be said that the probability of occurrence of hypertension in adults aged 26-45 years in Medan which obesity, is four times greater than those who are not obese. This is in line with the study of Rohkuswara (2016) in the city of Bandung with AOR = 1.681 and P-value = 0.031 [18]. Obesity has become an epidemic today.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, North Sulawesi Province is always in the first rank with a prevalence of 24.1% in 2013 and 30.2% in 2018 3,10 . The prevalence close to results in this study can be seen in a research by Integrated Development Post for Non-Communicable Disease of Port Health Office (POSBINDU PTM KKP) Bandung in 2016 on 202 samples showing that the proportion of overweight and obesity was 54.9% 6 . This is also in accordance with research which found that 53.61% of respondents are obese 19 .…”
Section: Discussionsupporting
confidence: 89%
“…Most young adults are in the Stage I hypertension category and are unaware of the condition. They then continue to be exposed to risk factors until the disease becomes more severe 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It was due to the feeling of inferiority felt after getting discriminatory behavior. Social factors related to ARV adherence were fear of using health services when taking ARV drugs, fear of being seen interacting with health care workers providing HIV services, fear of stigma and discrimination from society, and fear of being embarrassed by the community if their HIV status was revealed [14].…”
Section: Discussionmentioning
confidence: 99%